Integrasi Pendidikan Akhlak Dalam Kitab Akhlak Lil Banat Wal Banin Jilid 1 Pada Materi Akidah Akhlak Di Madrasah Tsanawiyah Kelas Viii Sebagai Bentuk Penguatan Refrensi Bahan Ajar - Nanang Abdillah; Zumrotul Farikha (Jurnal Pendidikan Agama Islam Miazhar, 2024)
One effort to instill moral education in students at school is through learning the Aqidah Akhlak. The researcher took the book Akhlaq Lil Banat Wal Banin by 'Umar bin Ahmad Baraja which is a book about morals, for this reason the researcher tried to make these two things relevant. The aim of this research is to describe: (1) The content of moral education in the book Akhlaq il banat wal banin by 'Umar bin Ahmad Baraja (2) The relevance of moral education in the book Akhlaq Lil Banat wal banin by 'Umar bin Ahmad Baraja' with material on Aqidah Morals in Madrasah Tsanawiyah class VIII. The research method used in this data analysis is library research with data collection techniques in the form of documentary techniques. Meanwhile, the data analysis technique used in research is content analysis which can be carried out on textbooks, both theoretical and empirical. From the research results it was found that: (1) The moral education values ​​contained in the book of Akhlaq lil Banat Wal Banin include moral values ​​towards Allah SWT and the Messenger of Allah, moral values ​​towards humans, moral values ​​towards oneself, moral values ​​towards the universe (2) The relevance of moral education in the book Akhlak lil banat wal banin by 'Umar bin Ahmad Baraja and the Aqidah Akhlak material in class VIII Madrasah Tsanawiyah.